Facilitators and barriers associated with youth player transition to professional first-team football: A key stakeholder perspective - McGuigan, M.; Dello Iacono, A.; McRobert, A.; Cowan, D.; Unnithan, V. B. (International Journal of Sports Science & Coaching, 2024)
The transition of elite youth footballers through academy systems towards the first team is highly complex, competitive, and often unsuccessful. A myriad of factors including technical competence, physical prowess, and the development environment combine to determine youth player progression. Current research has focused on broad investigations of multiple clubs and stakeholders, providing a valuable overview of the key aspects associated with elite youth player transition. This study aimed to provide an in-depth, context-specific investigation of key stakeholders within an elite level club in the United Kingdom (UK). Seven key stakeholders including the head of the academy (n = 1), the head of sports science (n = 1), coaches (n = 3), and lead sports scientists (n = 2) were recruited. Framework analysis led to the development of a practical framework outlining the key facilitators and barriers of youth-to-first-team transition. Facilitators of transition included overcoming adversity, high-level physical prowess, exceptional technical competence, and possessing at least one elite-level attribute. Barriers to transition included a lack of opportunity, lucrative youth player contracts and a lack of development-specific coaching. In addition, the developmental environment and developing individuals within a team environment were key influences on youth-to-first-team transition. This study complements recent broad investigations of the UK and global stakeholders by corroborating many of their findings while providing transferable, context-specific accounts of applied issues related to successful transition to first-team football.